Trends of mortality due to septicemia in Greece: an 8-year analysis. - Matthew E Falagas; Ioanna P Korbila; Anastasios Kapaskelis; Kyriaki Manousou; Lili Leontiou; Giannoula S Tansarli (PLoS ONE, 2013)
BACKGROUND: Infectious diseases are among the major causes of death worldwide. We evaluated the trends of mortality due to septicemia in Greece and compared it with mortality due to other infections. METHODS: Data on mortality stratified by cause of death during 2003-2010 was obtained from the Hellenic Statistical Authority. Deaths caused by infectious diseases were grouped by site of infection and analyzed using SPSS 17.0 software. RESULTS: 45,451 deaths due to infections were recorded in Greece during the 8-year period of time, among which 12.2% were due to septicemia, 69.7% pneumonia, 1.5% pulmonary tuberculosis, 0.2% influenza, 0.5% other infections of the respiratory tract, 7.9% intra-abdominal infections (IAIs), 2.5% urinary tract infections (UTIs), 2.2% endocarditis or pericarditis or myocarditis, 1.6% hepatitis, 1% infections of the central nervous system, and 0.7% other infections. A percentage of 99.4% of deaths due to septicemia were caused by bacteria that were not reported on the death certificate (noted as indeterminate septicemia). More deaths due to indeterminate septicemia were observed during 2007-2010 compared to 2003-2006 (3,558 versus 1,966; p<0.05). CONCLUSION: Despite the limitations related to the quality of death certificates, this study shows that the mortality rate due to septicemia has almost doubled after 2007 in Greece. Proportionally, septicemia accounted for a greater increase in the mortality rate within the infectious causes of death for the same period of time. The emergence of resistance could partially explain this alarming phenomenon. Therefore, stricter infection control measures should be urgently applied in all Greek healthcare facilities.